2005
DOI: 10.1016/j.otohns.2005.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Excision versus Monopolar Electrosurgical Excision for Tonsillectomy

Abstract: OBJECTIVE: We previously compared radiofrequency (Evac) tonsillotomy with monopolar electrosurgical (Bovie) tonsillectomy and showed significantly less pain with the Evac. Tonsillotomy leaves a cuff of tonsil behind, the significance of which is unknown. We hypothesize that Evac tonsillectomy also is less painful than Bovie tonsillectomy. STUDY DESIGN AND SETTING: We compared Evac (ENTec Evac 70; ArthroCare, Sunnyvale, CA) and Bovie tonsillectomy in a prospective, blinded fashion. Each participant had 1 tonsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…In most of these studies, postoperative pain was significantly less in the coblation group [11,13,18,24]. A fifth study showed no difference in pain between the two procedures [23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most of these studies, postoperative pain was significantly less in the coblation group [11,13,18,24]. A fifth study showed no difference in pain between the two procedures [23].…”
Section: Introductionmentioning
confidence: 99%
“…There are various studies describing the use of coblation in tonsillectomy with varying conclusions regarding intraoperative blood loss, postoperative hemorrhage rates, postoperative pain, and healing rates [12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While each modality promises a reduction in the recovery time and morbidity associated with tonsillotomies, each has its potential drawbacks and various rates of tonsillar regrowth. They are discussed at greater length elsewhere [11][12][13][14][15]. In a search for a less invasive and more efficacious technique, Koltai et al developed PIT, which utilizes a microdebrider for resection [10].…”
Section: Discussionmentioning
confidence: 99%
“…In juxtaposition, electrocautery, diathermy, or laser temperatures are significantly high (750–900°C) and result in significant heat propagation far in excess of the therapeutic needs [33, 34.] The radiofrequency waves have a property of sealing small blood vessels while dissecting the tissues without creating any char [35, 36]. Use of electrocautery or diathermy invariablyresults in burning of the adjacent healthy tissues and causes more pain and delay in wound healing [37].…”
Section: Discussionmentioning
confidence: 99%